THE IMPLEMENTATION OF THE PROBLEM-BASED LEARNING MODEL TO IMPROVE CRITICAL THINKING SKILLS IN SOCIAL STUDIES LEARNING (A CLASSROOM ACTION RESEARCH IN CLASS VII-I OF SMPN 2 SAMARANG): Classroom Action Research in Class VII-I SMPN 2 Samarang - Nurrahmawati, Dewi Sri; Tetep; Dianah, Lili (SAHUR Journal, 2025)
The critical thinking ability of seventh-grade students in class VII-I at SMPN 2 Samarang is still relatively low, especially in social studies learning. This is evident from the pre-cycle critical thinking ability test results, which were 43%. This may be due to the use of the lecture model in teaching, which does not actively involve students in the learning process. The Purpose of this research is to improve students' critical thinking skills in social studies learning by implementing the Problem-Based Learning model for class VII-I students at SMPN 2 Samarang. The research method used is Classroom Action Research (CAR), conducted in two cycles with four stages: planning, implementation, observation, and reflection. The data analysis technique involves comparing students' critical thinking abilities between the first and second cycles, illustrated by test results conducted at the end of each learning session.. The results of the Classroom Action Research (CAR) indicate that in the first cycle, students' critical thinking skills improved to 57% with an average score of 69,6. Furthermore, in the second cycle, the percentage of critical thinking ability increased to 86% with an average score of 80,4. Thus, it can be concluded that the application of the Problem-Based Learning model can enhance students' critical thinking skills in social studies learning for class VII-I at SMPN 2 Samarang.